BETWEEN HOBBY AND CRIME: CRIMINAL LIABILITY FOR AIR GUN POSSESSION - Ahmad Syaifudin; Yuli Dian Fatmawati; Sunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Air gun ownership in Indonesia is often seen as part of a shooting hobby or recreational sport. However, in practice, air guns also have the potential to be misused, posing a threat to public order and public safety. The main issues in this study are the boundaries between air gun ownership as a legitimate activity and acts that can be qualified as criminal offenses, as well as the forms of criminal liability that can be imposed on the owner. This study aims to analyze the legal regulation of air guns in Indonesian legislation and examine the application of criminal liability for their ownership and misuse. The research method used is normative juridical with a statutory and conceptual approach, through a review of police regulations, the Criminal Code, and relevant court decisions. The results showed that the ownership of an air gun is not automatically a criminal offense, as long as it meets the licensing requirements and is used according to its designation. However, unlicensed possession or use that causes threat, injury, or public unrest can lead to criminal liability. This study emphasizes the importance of legal certainty and supervision to keep air guns within the realm of safe and responsible hobby.